Tinjauan Hukum Pidana Islam Terhadap Sanksi Bagi Pelaku Pemerkosaan Anak; Analisis UU. No 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Regi Kinaryosi; Iwan Iwan (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to analyze the sanctions imposed on perpetrators of child rape from the perspective of Islamic criminal law and to compare them with the provisions contained in Law Number 12 of 2022 concerning Sexual Violence Crimes. This research is motivated by the need to assess the extent to which the national legal system accommodates the principles of moral and spiritual justice emphasized in Islamic law. The methodology employed is normative legal research using a library research approach and a comparative case approach. The data sources consist of primary legal materials such as laws and court decisions, as well as secondary legal materials including literature on criminal law and both classical and contemporary fiqh texts. The findings reveal that Islamic criminal law provides a more comprehensive basis for imposing sanctions, as it emphasizes the protection of honor (al-‘irdh) and life (al-nafs), through the application of hudud or ta‘zir punishments to achieve substantive justice. Meanwhile, Law No. 12 of 2022 is more oriented toward procedural justice and victim protection. Therefore, integrating Islamic legal values is essential to strengthen both the effectiveness and moral dimensions of law enforcement against perpetrators of child rape.